Decision working medium for lower cycle CCGT trinary type; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Tsibulskiy S. A. Svyatoslav Anatolievich; Galashov N. N. Nikolay Nikitovich; Bannova A. I. Albina Ilgizovna; Melnikov D. V. Denis Vladimirovich; Kiselev A. D. Aleksandr Dmitrievich (2017, 2017)
Title screen